The Strategy of Observing, Imitation, and Modification in The Preparation of Lesson Plan in Microteaching Practice - Dina Ramadhanti; Diyan Permata Yanda (Universitas Pahlawan Tuanku Tambusai, 2021)
The lesson plan is one of the determining factors for the success of the learning implementation. Lesson plans are a major part of the microteaching practice cycle. However, in the practice of microteaching, lesson plans are not more important than the practice of basic teaching skills so that student-teacher is not skilled in preparing lesson plans. In preparing the lesson plans, observing, imitation, and modification strategies are used so that the research subjects can prepare lesson plans according to the components of the lesson plans that integrate 21st Century skills. This study is a one-group experimental study to determine the difference in average learning outcomes before and after using observing, imitation, and modification strategies. The results showed that the study subjects' learning outcomes after using the observing, imitation, and modification strategies were better than before using the observing, imitation, and modification strategies. This strategy is effectively used because it is able to increase the understanding and creativity of research subjects towards the preparation of lesson plans. In the practice of microteaching, the preparation of lesson plans needs to be a major concern before student teacher candidates practice basic teaching skills.